Prevalence of Enterobacteriaceae Producing Extended Spectrum Beta-Lactamase (ESBL) in Broiler Meat (Gallus domesticus) Sold in Regional Markets of West Surabaya - Risnanda, Kadek Rio; Masfufatun, Masfufatun; Listyawati, Agusniar Furkani; Kuntaman, Kuntaman; Sudibya, Akhmad (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Broiler meat is a foodstuff that is easily damaged by bacterial growth. Several pathogenic bacteria from the Enterobacteriaceae family have also been found as contaminants in chicken meat. While Extended Spectrum Beta-Lactamases (ESBL) are enzymes that have the ability to hydrolyze antibiotics of the penicillin class, first, second, and third generation cephalosporins as well as the monobactam group. Based on this phenomenon, the researchers wanted to examine the prevalence of the ESBL-producing Enterobacteriaceae family in broiler chicken (Gallus domesticus) meat sold in the West Surabaya market. This research is a descriptive observational type using a cross-sectional approach. The population in this study was broiler chicken meat taken from broiler traders in several markets in West Surabaya which had met the inclusion and exclusion criteria with a large sample of 50 samples. Then the data were analyzed using the chi-square test. The results of the analysis showed that 13 samples produced ESBL. The prevalence of Enterobacteriaceae bacteria producing ESBL in broiler chicken (Gallus domesticus) meat in several markets in West Surabaya is 26% of the 50 samples used. The results of the chi-square test showed that there was no significant difference between locations where ESBL was found.